Highly sensitive spectrophotometric method for the determination of vanadium in environmental, biological, food and soil samples using orthoaminophenol - Zannat, Tasnima; Ahmed, Mohammad Jamaluddin (European Journal of Chemistry, 2015)
A simple, ultra-sensitive and highly selective non-extractive spectrophotometric method for the determination of trace amount of vanadium(V) using orthoamino phenol (OAP) has been developed. OAP reacts in highly acidic (0.005-0.015 mol/L H2SO4) and aqueous media with vanadium(V) to give a chocolate color chelate which has an absorption maximum at 405 nm. The reaction was instantaneous and absorbance remains stable for over 72 h. The average molar absorption co-efficient and Sandell’s sensitivity were found to be 6.7×105 L/mol.cm and 10 ng/cm2 of vanadium(V), respectively. Linear calibration graphs were obtained for 0.02-50.00 mg/L having detection limit 1 µg/L and quantification limit of the reaction were found to be 10 µg/L and RSD 0-2%. The stoichiometric composition of the chelate is 1:3 (Vanadium(V):OAP, v:v). Large excess of over 60 cations, anions and complexing agents (Like tartrate, EDTA, oxalate, chloride, phosphate, thiourea, SCN- etc.) do not interfere in the vanadium determination. The method was successfully used in the determination of vanadium in several standard reference materials (Alloys and steels) as well as in some environmental waters(Potable and polluted), biological samples (Human blood and urine), food samples, soil samples, solution containing both vanadium(IV) and vanadium(V) and complex synthetic mixtures. The results of the proposed method for biological analyses were found to be in excellent agreement with those obtained by AAS. The method has high precision and accuracy (s = ±0.01 for 0.5 µg/mL).